Case report: A rare case of neutropenia caused by pembrolizumab in squamous lung cancer and literature review - Tan, Qiaoyun; Liu, Lichao; Huang, Yu; Dong, Xiaorong; Chen, Lingjuan (Frontiers in Oncology, 2022)
Background Immune checkpoint inhibitors, including anti-PD-1 therapies, have prolonged overall survival in patients with a variety of cancers, and immunotherapy is sometimes associated with immune-related adverse events (irAEs); however, hematological toxicity, especially neutropenia, is rare. Case presentation A 78-year-old man with squamous lung cancer, with brain metastasis, was treated with pembrolizumab and albumin-bound paclitaxel as first-line treatment for one cycle and changed to pembrolizumab plus anlotinib at the second cycle. After two therapy cycles, grade 4 neutropenia developed, which mainly contributed to irAEs. The patient was started on granulocyte colony-stimulating factor (G-CSF) but did not improve; he was then treated with corticosteroids, and neutrophil counts gradually returned to normal levels. However, the patient eventually died because of neurological problems. Conclusion Grade 4 neutropenia associated with ICI, although rare, is often severe and presents with infectious complications; it needs to be diagnosed early, and clinicians should ensure prompt and proper management to such patients.